Ciclologística: avaliação do uso de bicicletas elétricas na logística de última milha nas operações postais - Moura, Frank Schneider Carvalho de (2023)
The context of smart cities, a trend of increasing relevance in directing the strategies of public administrators, citizens and companies, generates the need for investment in lastmile logistics solutions that are more environmentally friendly and integrated into the urban scenario, especially in large cities. The present study, conducted as action research, quantitative and qualitative, applied and descriptive, was based on a sample of the routes traveled by 27 electric cargo bicycles from Correios in the Federal District, which were in use for 1 year, between May 2021 and May 2022 in postal operation in that location, evaluates whether the use of electric bicycles is more productive on the routes analyzed, simulates the potential for use in the Post Office, in addition to the potential environmental gain of this technology in the last mile process in the postal service. The assessment of the operational and environmental feasibility of investing in cycle logistics, based on an electromobility initiative using electric bicycles, as an alternative to improving the performance of deliveries of correspondence and small parcels originating from e-commerce, sought to assist the postal operator, and logistics companies in general, to direct their strategic actions towards a context of solutions that better integrate the delivery of goods to urban environments in large cities. Based on the collection of route data from the Correios route georeferencing system, and treatment of the database with a structured statistical analysis anchored in the Python language, it was possible to analyze performance indicators, being the number of objects per day for each postman and number of objects delivered per distance covered were the key indicators adopted, enabling the simulation of the expanded use of this equipment and the environmental gain of electric bicycles in the last mile of the Post Office. The study proved operational viability, with a 40% increase in delivery productivity, and environmental viability, with a potential reduction of 82 tons of CO2 per month, in addition to a simulation of the expansion of technology in the national postal service, with an indication of the possibility of use of around 5,700 electric bicycles at the Post Office